2015
DOI: 10.1016/j.cgh.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Nonalcoholic Fatty Liver Disease and Progression to Cirrhosis Are Associated With Atherogenic Lipoprotein Profile

Abstract: Background & Aims Nonalcoholic fatty liver disease (NAFLD) is independently associated with increased cardiovascular mortality. Although NAFLD is associated with dyslipidemia, it is not clear whether recently identified markers of cardiovascular risk indicate liver disease progression in patients with histologically confirmed NAFLD. We evaluated an extensive panel of serum markers of cardiovascular risk in non-diabetic patients with histologically proven NAFLD. Methods We performed a case–control study in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
154
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 29 publications
9
154
3
2
Order By: Relevance
“…A reciprocal relationship between hepatic steatosis and adipose tissue insulin resistance has been demonstrated in nontransplant patients. 8 This results when increasing insulin resistance at the level of adipose tissue results in incomplete suppression of adipose tissue lipolysis. Therefore, increase in adipose tissue lipolysis results in increased generation of FFAs, which then serve as a substrate for hepatic triglyceride production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A reciprocal relationship between hepatic steatosis and adipose tissue insulin resistance has been demonstrated in nontransplant patients. 8 This results when increasing insulin resistance at the level of adipose tissue results in incomplete suppression of adipose tissue lipolysis. Therefore, increase in adipose tissue lipolysis results in increased generation of FFAs, which then serve as a substrate for hepatic triglyceride production.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] A recent study showed that the presence of hepatic steatosis was significantly associated with proatherogenic abnormalities that was independent of traditional risk factors of CVD risk (ie, age, sex, body mass index [BMI]). 8 Liver transplantation (LT) is the definitive therapy for end-stage liver disease and has excellent long-term survival because of improvements in immunosuppression and infection control. Similar to CLD, CVD is an important cause of long-term mortality in liver transplantation recipients (LTRs).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…167,168 This finding may be of potential significance in differentiating simple steatosis from NASH 167 and suggests that most hyperlipidemic patients with increased non-HDL cholesterol levels are potential candidates to liver biopsy, given that they are more likely to develop NASH. Hepatic biosynthetic failure occurring in those developing cirrhosis will blunt the severity of the initial dyslipidemia [169][170][171] mirroring the disappearance of hepatic steatosis associated with the development of NASH-cirrhosis.…”
Section: Hyperlipidemia and Hypolipidemiamentioning
confidence: 99%